Multi converter approach to active power filtering using current source converters. - El Shatshat, R.
Active power filtering is performed by detecting the line current and voltage signals, generating a current equal-but-opposite to the distortion current using a power converter and injecting the compensating current into the power line. In such applications, it is desirable to combine high power and high switching frequency while minimizing the losses. This asks for special converter topologies and control techniques. In this paper, a multi-converter active power-line filter, based on current-source converter (CSC) modules, is proposed. The power rating and switching frequency of each CSC module is equal to those required for the filtering job divided by the number of modules. The control system utilizes two linear adaptive neurons (ADALINE's) to process the signals obtained from the line. The first ADALINE (the current ADALINE) extracts the harmonic components of the distorted line current signal and the second ADALINE (the voltage ADALINE) estimates the fundamental component of the line voltage signal. The outputs of both ADALINE's are used to construct the modulating signals of the filter modules. The proposed modular active filter offers the following advantage: (1) high efficiency due to low conduction and switching losses; (2) high reliability; and (3) high serviceability. The proposed active power-line filter treats the AC system on a per-phase basis, has fast response and adapts to the load variations. Theoretical expectations are verified by digital simulation using EMTDC simulation package
Keywords: EMTDC simulation package; PWM Converter; Active power filtering; Compensating current injection; Current ADALINE; Current source converters; Current-source converter modules; Digital simulation; Distortion current; Harmonic components; High efficiency; High power; High reliability; High serviceability; High switching frequency; Line current signals detection; Linear adaptive neurons; Losses minimization; Low conduction; Modular active filter; Modulating signals; Multi converter approach; Multi-converter active power-line filter; Power converter; Power rating; Switching frequency; Switching losses; Voltage ADALINE; Voltage signals detection